Subsecond Annealing of Advanced Materials Annealing by Lasers, Flash Lamps and Swift Heavy Ions - Skorupa, Wolfgang; Schmidt, Heidemarie; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
The thermal processing of materials ranges from few femtoseconds by Swift Heavy Ion Implantation to about one second using advanced Rapid Thermal Annealing. This book offers after an historical excursus selected contributions on fundamental and applied aspects of thermal processing of classical elemental semiconductors and other advanced materials including nanostructures with novel optoelectronic, magnetic, and superconducting properties. Special emphasis is given on the diffusion and segregation of impurity atoms during thermal treatment. A broad range of examples describes the solid phase and/or liquid phase processing of elemental and compound semiconductors, dielectric composites and organic materials.
From the Contents: The very early time -- Nanonet formation by constitutional supercooling of pulsed laser annealed, Mn-implanted germanium -- Metastable activation of dopants by solid phase epitaxial recrystallization -- Superconducting Ga-implanted Germanium -- Structural changes in SiGe/Si layers induced by fast crystallization.
Keywords: Materials science; Semiconductors; Surfaces (Physics).; Interfaces (Physical sciences).; Thin films; Lasers; Photonics; Microwaves; Optical engineering; Optical materials; Electronic materials; Materials Science; Optical and Electronic Materials; Laser Technology, Photonics; Semiconductors; Microwaves, RF and Optical Engineering; Surface and Interface Science, Thin Films; Electronic books